Wide frequency domain modeling method of DCTV based on rational function approximation. (28th February 2021) - Zuo, Hang; Li, Xiaopeng; Xu, Fangwei; Shu, Qin
Summary: DC voltage transformer (DCTV) is an important device for measuring the voltage of ultra‐high voltage direct current (UHVDC) transmission system. Its characteristics of wide frequency transmission directly affect the accuracy of voltage measurement. In order to solve the problem of large harmonic voltage measurement errors caused by the inaccurate acquisition of the broadband transmission characteristics of DCTV, a new broadband modeling method for DCTV is proposed in this paper. This article proposes a new DCTV wide frequency domain modeling method without relying on DCTV parameters. The DCTV transfer function values at different frequencies are obtained by measurement, and the error function is constructed based on the rational approximation fitting principle. Then, the particle swarm optimization algorithm is used to iteration the error function to obtain the optimal solution and to fit the expression of transfer function. The accuracy of the algorithm is studied in different frequency sampling range (low frequency, intermediate frequency, and high frequency) and noise levels. Simulations based on actual DCTV parameters verify that the proposed method has a relative error of only 2.1908e‐16% within the 200th harmonic. It has strong anti‐noise ability and can control the error within 5% when the SNR of sampling value is greater than 1 dB. Abstract : After running for a long time, the frequency characteristic calculated by the rated parameter has a large error with the frequency characteristic in actual work. The frequency characteristic obtained by using the rational function approximation method proposed in this article can reflect the frequency characteristic of DCTV in actual work more accurately.